Psychosocial treatment preferences of persons living with young-onset dementia and their partners. (January 2022) - Grunberg, Victoria A; Bannon, Sarah M; Reichman, Mira; Popok, Paula J; Vranceanu, Ana-Maria
Persons living with young-onset dementia and their partners often experience elevated emotional distress as they cope with an unexpected progressive illness during an active life stage (typically ages 45–64 years). Despite their heightened emotional distress, psychosocial resources are both limited and lack the specificity to meet the unique needs of both partners. Our aim was to gain an in-depth understanding of the psychosocial treatment preferences of persons with young-onset dementia and their partners—an important first step in developing a tailored intervention. We conducted semi-structured dyadic interviews with persons with young-onset dementia and their partners ( N = 23) and used a hybrid deductive–inductive approach to thematic analysis. We identified 12 themes across four domains: (1) perceptions of available and lacking resources, (2) preferences for program content, (3) preferences for program format, and (4) barriers and facilitators to participation. Couples indicated there is a lack of specific and family-oriented resources, which can create more stress and relationship strain. Couples endorsed support for a virtual, dyadic intervention delivered shortly after diagnosis focused on providing tools to cope with difficult emotions and symptom progression and enhance communication and meaningful daily living. They also identified potential barriers to program participation and offered suggestions to promote engagement. By using a qualitative approach, we were able to gather nuanced information that can be used to directly inform a feasible, accepted, and person-centered psychosocial intervention for persons with young-onset dementia and their partners.